2023
DOI: 10.3390/su151411446
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Trait Selection of Quinoa Ideotypes at Different Levels of Cutting and Spacing

Abstract: Climate change has affected the food supply chain and raised serious food concerns for humans and animals worldwide. The present investigation aimed to assess the effect of environmental factors along with three different levels of cutting (i.e., cutting 1, 2, and 3 at the vegetative, budding, and flowering stages, respectively) and spacing (i.e., 21, 23, and 26 cm) on quinoa biomass and quality to select the most suitable accessions. This experiment was repeated for two years using a split–split plot experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 70 publications
0
0
0
Order By: Relevance
“…According to the results, we found that the selection based on MGIDI provided satisfactory gain. The measured MGIDI, based on the BLUP data from multiple traits in two years, selected 20 resistant genotypes (17,80,111,127,81,38,37,61,132,59,Dorfak,58,46,141,18A,54,27,140,51,and 32) that highly overlapped with selected genotypes using cluster analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the results, we found that the selection based on MGIDI provided satisfactory gain. The measured MGIDI, based on the BLUP data from multiple traits in two years, selected 20 resistant genotypes (17,80,111,127,81,38,37,61,132,59,Dorfak,58,46,141,18A,54,27,140,51,and 32) that highly overlapped with selected genotypes using cluster analysis.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, they are becoming more prevalent among plant breeders for precise genotypic value estimation [32]. Also, this method is free from the multi-collinearity problem [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation